Handling Of Pt Citilink Indonesia Domestic Irregularity Cargo At Soekarno Hatta Airport - Evaf Maulina; Dewi Dyah Widyastuti; Susi Arijanti; Tri Susilowati; Bekti Setiadi (Universitas Ibn Khaldun Bogor, 2023)
As per Carrier-set fees apply to products sent by ship or airline (cargo is not the same as checked baggage). The SMU (air cargo letter) is used for domestic flights, while the AWB (air waybill) or B/L (bill of landing) is used for international flights or cargoes. The shipper, the carrier, and the consignee are the major stakeholders engaged in the shipping of cargo. Cargo that encounters anomalies is sometimes referred to as irregularity cargo during the receiving or shipping process. As long as they don't follow the relevant standard operating procedures, commodities are considered irregular if they cause problems throughout the receiving or shipping process. One of Garuda Indonesia's primary subsidiaries and a low-cost carrier in Indonesia is Citilink. Contrary to its more affordable rivals, Citilink nevertheless places a high priority on customer service and safety, whereas they occasionally compromise on these aspects to provide lower fares.